Phantom thread [videorecording (DVD)] - Anderson, Paul Thomas; Day-Lewis, Daniel; Manville, Lesley; Krieps, Vicky, 1983- (Universal Pictures Home Entertainment, 2018)
Set in the glamour of the 1950's post-war London, renowned dressmaker Reynolds Woodcock and his sister Cyril are at the center of the British fashion, dressing royalty, movie stars, heiresses, socialites, debutants and dames with the distinct style of The House of Woodcock. Women come and go through Woodcock's life until he comes across a young, strong-willed woman, Alma, who soon becomes a fixture in his life as his muse and lover. Once controlled and planned, he finds his carefully tailored life disrupted by the scariest curse of all...love.